Analysis of the Anti-Fraud Status of the US Dollar Clearing System and International Practice Reference - Xiao, Qing (Journal of Global Economy, Business and Finance, 2025)
Based on the current international financial background and focus, this paper conducts a comprehensive analysis and review of the basic framework, operation mechanism, types and traits of fraud in the US dollar clearing system. From the perspective of China’s financial risk prevention, it conducts necessary empirical research, analysis and discussion on the current situation of anti-fraud in financial institutions, the risk countermeasures of regulatory authorities, fund recovery and risk prevention. On this basis, it puts forward corresponding countermeasures and suggestions for the construction and improvement of China’s anti-fraud system, policy design and implementation strategies.